2015
DOI: 10.3892/ol.2015.3078
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 3, subunit C is overexpressed and promotes cell proliferation in human glioma U-87 MG cells

Abstract: Abstract. Disrupted protein translation is prevalent in tumours. Eukaryotic translation initiation factors (eIFs) were found to play an important role in various tumours. However, the involvement of eIFs in glioma remains to be elucidated. The present study explored the expression and the role of eIF 3, subunit C (eIF3c) in human glioma. The expression of eIF3c in glioma tissues was evaluated by immunohistochemistry. The impact of eIF3c inhibition on U-87 MG was explored in vitro and in vivo by lentivirus-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…A lentiviral system of siRNA was used to depress EIF3C expression, as previously described [ 15 ]. The targeting siRNA sequence was gtcactaaaggtctgttta designed in the website ( www.invivogen.com/sirnawizard/ ), and homologous negative control siRNA was ttctccgaacgtgtgtgtacgt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lentiviral system of siRNA was used to depress EIF3C expression, as previously described [ 15 ]. The targeting siRNA sequence was gtcactaaaggtctgttta designed in the website ( www.invivogen.com/sirnawizard/ ), and homologous negative control siRNA was ttctccgaacgtgtgtgtacgt.…”
Section: Methodsmentioning
confidence: 99%
“…Components of EIF3 complex are required for several steps in the initiation of protein synthesis [ 12 , 13 ]. In the past few years, it has been reported that EIF3C is essential for cell proliferation in various human tumors, such as glioma [ 14 , 15 ], hepatocellular carcinoma [ 16 ], testicular seminomas [ 17 ], meningioma [ 18 ], and colon cancer [ 19 , 20 ]. Downregulated EIF3C may result in switching off polysomes and inducing cell death due to translation depressed at the initiation stage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that inhibition of eIF3C in vitro using siRNA reduces cell proliferation, decreases colony formation, increases apoptosis and promotes cell cycle arrest in U87MG cells. Finally, these authors showed that lower eIF3C expression reduces tumor growth in vivo using a glioma xenograft mouse model [75].…”
Section: Eif3mentioning
confidence: 99%
“…Unfortunately, REMBRANDT and TCGA databases on Betastasis do not encompass the expression of EIF3C (Table 1). Nevertheless, eIF3C together with other eIF3 subunits have been studied in glioma tissues, in vitro and in vivo by other research teams [74][75][76][77][78].…”
Section: Eif3mentioning
confidence: 99%
“…Recently, it has been reported that eIF3 selectively binds to mRNA related to cell proliferation and controls their translation [30]. Importantly, eIF3c is essential for cell proliferation in various human tumors [31–37]. However, it remains to be addressed whether eIF3c is involved in the resistance to anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 99%